ANALISIS PERBEDAAN ETNIS JAWA - CINA (TIONGHOA) DALAM COMPLAINT CONSUMER BEHAVIOR AND INTENTIONS TERHADAP JASA PELAYANAN RUMAH SAKIT DI SURAKARTA - Chuzaimah Chuzaimah; Moechamad Nasir (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2012)
By understanding unsatisfaction and also its effect research to complaint behavior havecome to critical factor for company of penetrating strategy pursuer business market. Which salesmore tend to customer existence becoming key in getting profit. This research pursuant at empiricinvestigation designed to compare the complaint consumer behavior and intentions in a culture atethnical of Chinese ( Tionghoa) by consumer is behavior and intentions at ethnical of Java. Theresult of this research is Ethnical culture of Java, none a passive culture. attitude of relatedComplaint consumer research and conducted more than three decade ago have made clear it thatregardless of culture about market which they run the, hospital which do not plan the way ofeffective about relation by complaint consumer behavior which is laid open by voice responses willharm the sale, sooner or later. Same Hold fact for the attitude of consumer sigh expressed byprivate responses, any way, such as those which shown in researching into this, bigger challengein the first place in market with expressed by a ethnical culture of Java. Also customer in anethnical culture of Java do not voice the complaint to hospital, this matter did not mean that theydo not express themselves. If them dissatisfy, they possible have a share in private responses(leaving or negative communications ) and conducive to the third party responsesTheir residency simply possible their disinclination to express the negative emotion, like griping,to external group. But this matter is clear the than study that they do their expression throughother channel, like with the inner group.